Caffeic acid phenethyl ester (CAPE): pharmacodynamics and potential for therapeutic application - Yordan Yordanov (Pensoft Publishers, 2019)
Caffeic acid phenethyl ester (CAPE) is the major pharmacologically-active component of some propolis types, rich in polyphenols, such as poplar propolis types. CAPE has the potential to be applied as a pharmaceutical as it possesses most of the pharmacological activities of propolis, such as anti-proliferative, antioxidant, immunomodulatory, antidiabetic, anti-inflammatory and antimicrobial. Its advantage is that it lacks some of the downsides of total propolis extracts, such as inability for unified standardization, which is cornerstone for implementing its therapeutic potential as a drug. The current paper provides an overview on the pharmacodynamic principles of CAPE. We present literature search outcomes form ClinicalTrials.gov database and from scientific publications, available on Scopus and Crossref databases. We take a round view of CAPE's potential therapeutic implications in light of approved drugs with related modes of action.